A Critique of Certain Half Plane Diffraction Analyses - Senior, Thomas B.A. (Electromagnetics, 1987)
When solving the diffraction problem of an electromagnetic wave incident on a half plane subject to a mixed boundary condition, the analysis can be simplified by using the field components normal to the surface. Although this is the procedure generally employed, it is shown that the Wiener-Hopf analysis may involve quantities whose edge singularities are non-integratable, and whose Fourier transforms do not exist in the classical sense. A method for overcoming the difficulty is presented.